Tribute to Professor Bernardo A. Houssay - Acevedo, Darío (2014)
Keynote address delivered by Professor of Human Physiology, Dr. Dario Acevedo, at the solemn session of the Faculty of Medicine, February 27, 1948, when he joined the Dr. Bernardo A. Houssay as honorary professor of the Faculty of Medicine and Science, National University of San Marcos.